Educational Improvement Through External Consultancy: The Difficult Road Towards Sustainability [Mejora Educativa a Partir de Asesoría Externa: El Complejo Camino Hacia la Sostenibilidad] - Rios-Munoz, D; Villalobos-Vergara, P (Universidad Austral de Chile, 2016)
This article shows a study which, firstly, attempts to reveal the achievements of four public high-schools receiving technical consultancy from the perception of school actors, three years after the assistance took place. Secondly, it includes the monitoring made a year later to the institution presenting improvement sustainability. This is a qualitative study which used interviews and focus groups with teachers and directive teams. Results show that institutions showing a sustainable improvement had directive leadership, autonomy, systematization of work, positive work environment and collaborative work as the key of their success. The lack of resources, the negative work environment, the indifference of leadership succession, the lack of commitment with the proposal, and the negative expectation on the students represented hinders for a sustainable improvement.